Trapped between narcos and the State: the forms of Civil Resistence in México (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
In today's Mexico, civil society finds itself between a State unable to protect the rights of its citizens - either for complicity, omission or negligence - and an increasingly ruthless and violent organized crime. This essay aims to investigate some forms of civil resistance born as a result of the current situation in Mexico. Given the escalation of violence that the country has experienced in recent years, the alarming number of murders related to drug trafficking and the continued disappearances of innocent people, special attention is devoted to the movement of the victims' families, the most urgent reality to address. In addition, experiences related to defending the rights of the weakest social components, in particular children and adolescents, women and migrants, are explored. Social journalism and freedom of expression are also discussed.